The Adaptability in the Reign of Rome - Nur Aifiah Binti Ibrahim (Program Magister Pendidikan Sejarah FISH UNJ, 2026)
The life they live reflects a godlike resilience, forged in the balance between light and darkness. Having endured the worst, they learned what is best for building a strong and compassionate community in the future. Their once-empty dreams are now fulfilled by the encouragement and cheers of the crowd. In pursuit of the life they once aspired to achieve, they attended a scholarly institution to shape their destiny. Their historical experiences, marked by sorrow, have the power to move people to tears while uplifting those who seek emotional and personal stability. Thus, their cultural background unites every part of their journey, guiding them toward their true purpose. The emotional reunion with loved ones becomes a defining moment—one capable of changing their lives forever.